2004
DOI: 10.1051/0004-6361:20040536
|View full text |Cite
|
Sign up to set email alerts
|

Continuous star formation in IZw18

Abstract: Abstract. We study the dynamical and chemical evolution of a galaxy similar to IZw18 under the assumption of a continuous star formation during bursts. We adopt a 2-D hydrocode coupled with detailed chemical yields originating from SNeII, SNeIa and from single intermediate-mass stars. Different nucleosynthetic yields and different IMF slopes are tested. In most of the explored cases, a galactic wind develops, mostly carrying out of the galaxy the metal-enriched gas produced by the burst itself. The chemical sp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
63
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(68 citation statements)
references
References 89 publications
5
63
0
Order By: Relevance
“…The chemical evolution is usually not very detailed in these models. Recchi et al (2001Recchi et al ( , 2002Recchi et al ( , 2004 provided detailed information on the ejection efficiencies of single chemical species produced by SNe (of both Type II and Type Ia) and by winds from intermediate-mass stars. RH07 added important information on the effect of clouds.…”
Section: A Brief Overview Of Literature Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The chemical evolution is usually not very detailed in these models. Recchi et al (2001Recchi et al ( , 2002Recchi et al ( , 2004 provided detailed information on the ejection efficiencies of single chemical species produced by SNe (of both Type II and Type Ia) and by winds from intermediate-mass stars. RH07 added important information on the effect of clouds.…”
Section: A Brief Overview Of Literature Resultsmentioning
confidence: 99%
“…The chemical enrichment of the galaxy is followed in detail; the production (by SNe of Type II, Type Ia, and intermediate-mass stars) of eight chemical elements (H, He, C, N, O, Mg, Si, and Fe) is considered, and the advection of these elements is followed by means of passive scalar fields. For instantaneous bursts, this scheme is described in detail in Recchi et al (2001) and its extension to more complex SFHs is explained in Recchi et al (2004). Since the code keeps correct track of the evolution of the metallicity in each computational cell, the detailed metallicity-dependent cooling function of Böhringer & Hensler (1989) can be implemented.…”
Section: The Chemo-dynamical Codementioning
confidence: 99%
“…Most importantly, the discrepancy between the observational results complicates the interpretation of chemical evolution models. Recchi et al (2004) found that abundances in the H  medium (defined by a temperature lower than 7000 K) should be similar to those in the H  gas. A definitive observational constraint is needed to challenge the models.…”
Section: Introductionmentioning
confidence: 90%
“…Throughout this work, we assume chemical homogeneity (instantaneous mixing), such that outflows caused by feedback processes are assumed to have the same metallicity as the interstellar medium, though in reality the situation cannot be captured by our simple recipe (Strickland & Heckman 2009) and newly produced metals are more likely to be ejected than the gas (e.g. Recchi et al 2004). Note that, thanks to the fine sub-stepping used for the stellar evolution, also ejecta from SNII and the contributions of single low-mass stars is implemented without the need to assume the istantaneous recycling approximation.…”
Section: Chemical Evolutionmentioning
confidence: 99%